The Use of Frozen and Deglycerolized Red Blood Cells. (5th September 2018) - Cap, Andrew; Badloe, John; Woolley, Thomas; Prat, Nicolas; Gonzales, Richard; Malloy, Wilbur; Taylor, Audra; Corley, Jason; Pidcoke, Heather; Reade, Michael; Schreiber, Martin
Abstract: Deglycerolized red blood cells have been used by the U.S. military for half a century, starting with the Vietnam War. Deglycerolized red blood cells have a frozen storage life of 10 years, but require special equipment to thaw and deglycerolize. The available data show no difference in either efficacy with complications when compared to standard product red blood cells.